Risk Factors of Hemophagocytic Lymphohistiocytosis in Adults with Fever of Unknown Origin: A Retrospective Study - Tian F; Xie N; Sun W; Zhang W; Zhang W; Chen J; Ruan Q; Song J (International Journal of General Medicine)
Fangbing Tian,1 Nana Xie,1 Wenjin Sun,2 Wencong Zhang,1 Wenyuan Zhang,1 Jia Chen,1 Qiurong Ruan,3,* Jianxin Song1,* 1Department of Infectious Diseases, Tongji Hospital Affiliated to Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 2Department of Infectious Diseases, Ezhou Central Hospital, Ezhou, People’s Republic of China; 3Institute of Pathology, Tongji Hospital Affiliated to Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianxin Song, Department of Infectious Diseases, Tongji Hospital Affiliated to Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China, Email songsingsjx@sina.com Qiurong Ruan, Institute of Pathology, Tongji Hospital Affiliated to Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China, Email ruanqiurong@sina.comPurpose: Hemophagocytic lymphohistiocytosis (HLH) is a critical syndrome with a high mortality rate. In clinical practice, some patients with fever of unknown origin (FUO) can develop HLH, further complicating the diagnosis and treatment. However, studies on HLH in adults with FUO are limited. This study aimed to investigate the clinical characteristics of adult patients with FUO to facilitate the early identification of those at high risk of developing HLH.Patients and Methods: We collected data from hospitalized patients with FUO between January 2014 and December 2020. Risk factors for HLH in adults with FUO were analyzed using univariate and multivariate analysis.Results: A total of 988 patients with FUO were included in the study. The incidence of HLH in adults with FUO was 6.4%, with hematological tumors being the primary cause. Multivariate analysis indicated that skin rash and elevated alanine aminotransferase, total bilirubin, triglycerides, lactate dehydrogenase, and ferritin levels were independent risk factors for HLH in adults with FUO.Conclusion: This study revealed the incidence rate, etiology distribution, and risk factors for HLH in adults with FUO. Comprehensive assessment of clinical and laboratory data at admission can assist in the early identification of FUO patients at risk for HLH.Keywords: Hemophagocytic lymphohistiocytosis, fever of unknown origin, etiology distribution, risk factors